(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article provides information on the distribution, morphology, and biological characteristics of the medicinal plant Silybum marianum (milk thistle). It highlights its structure, medicinal properties, and the role it plays in human life. The study discusses the significance of the plant in agriculture, medicine, and industry, as well as its cultivation techniques and chemical composition. Additionally, the article examines the importance of milk thistle as a pharmaceutical raw material and its potential applications in food and spice production.